Innovative Dispute Resolution: The Application of Blockchain in Cross-Border E-Commerce Governance - Zuo, Xiangbin; Dahlan, Nur Khalidah; Ahamat, Haniff; Wu, Dan (Journal of Ecohumanism, 2024)
With the rapid development of cross-border e-commerce, issues such as product quality, logistics disputes, and after-sales service have become increasingly prominent. Traditional litigation and arbitration methods have many limitations in efficiency and cost, and there is an urgent need to find innovative solutions. As a cutting-edge technology, blockchain technology can potentially improve dispute resolution efficiency, reduce costs, and enhance trust, especially in cross-border e-commerce. First, the basic concepts of blockchain and smart contracts are introduced, and then the application advantages of blockchain in dispute resolution are analyzed. Combined with the practical cases of Alibaba and JD Global Shopping, the actual effects and challenges of technology implementation are discussed. The paper puts forward suggestions for promoting the widespread application of blockchain technology in cross-border e-commerce dispute resolution and looks forward to its future development prospects.